The use of short stories in improving reading skills - Irhamni, M. Nabil; Nuzula, Nurfidausi; Indah Mala Rohmana, Wahyu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study explores the effectiveness of short stories in improving reading skills among English as Foreign Language (EFL) learners, with a particular focus on the